Research on the Quality of Local Civil Servants In Vietnam - Anh, Mai; Dung, Vu Dinh (Journal of Ecohumanism, 2024)
Civil servants are those who use state power to perform public duties according to their professional fields and job positions. The quality of civil servants is reflected in the work results of civil servants serving the state and the people. Vietnamese law also stipulates the evaluation of civil servants based on the work results of the civil servants assigned to them; and to achieve such work results, individual civil servants must have good moral qualities, professional qualifications, and working capacity to meet the requirements of public service activities. In this study, the author identifies the factors of moral qualities, professional qualifications, and working capacity as the forming conditions that have an impact on work results - the quality of civil servants. The author builds a theoretical framework consisting of these 4 scales and conducts a survey of 300 leaders of commune-level government agencies to collect information to assess the quality of commune-level civil servants in Vietnam today. The survey was conducted in 3 provinces representing 3 regions of Vietnam, including Hai Duong province (North), Ha Tinh province (Central), Soc Trang province (South). The research results show that local leaders underestimate the practical working capacity of commune-level civil servants. From the conclusion of this research, the author discusses some policy contents to improve the quality of local civil servants in Vietnam.